Rwanda : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2013)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper for Rwanda. Rwanda's second Economic Development and Poverty Reduction Strategy (EDPRS 2) covers FY2013/14-2017/18. It builds on the lessons learned in the implementation of the EDPRS 1. Among the positive lessons, the authorities point to the importance of ownership of the strategy including aid-financed programs, home-grown initiatives, community-based solutions, and an adequate institutional and legal framework. The overall objectives of the EDPRS 2 are to accelerate growth and further reduce poverty, including extreme poverty.